(untitled) (Citizenship in Action: Extension and Culture Magazine, 2025)
The reduction in biodiversity as a result of various environmental disturbances imposes on federal institutes the need to promote efforts to increase the conservation of species and popularize access to scientific knowledge, narrowing the known distance between academy and the community, using, for example, strategies raising awareness among people through environmental education practices using dry preserved specimens. Thus, the objectives of this work were: to produce two taxidermied pieces of Amazonian fish, establishing their cost, to use them to promote an environmental education action with students from the Ruy da Silveira Britto municipal elementary school and to transfer the technology to the community (students and employees) of the House-School of fisheries. The final result of the pieces was good, using a wooden base for support and presentation. The opportunity cost was recorded at R29.77 and the total cost of inputs was R11.10 and R17.97, respectively for aracu and tilapia. The final pricing must also include travel expenses to purchase materials, shipping costs for delivering the final product and any other expenses, in addition to considering the market and the desired profit margin. Fish was the most expensive item, which should motivate professionals to choose species with lower value, avoiding species with commercial appeal, such as tilapia. The lecture with slides and presentation of the taxidermied pieces had a lot of interaction with the elementary school students and the workshop stage was productive with 100% satisfaction, except for the location/environment, which, being hot, caused thermal discomfort in the afternoon. It was concluded that maintaining a collection of taxidermied fish parts requires constant monitoring and hygiene as a way of avoiding infestations and damage, being a very useful and valuable resource in environmental awareness, as well as an alternative income, since there is demand in places tourist attractions in the city. It is a possibility for people who have patience and care – necessary skills in carrying out the work – and availability of time, or even people who cannot be formally employed.